PENGARUH PENAMBAHAN MADU TERHADAP MUTU YOGHURT JAGUNG (Zea mays Indurata) - R Nofrianti; F Azima; R Eliyasmi (Indonesian Food Technologists, 2013)
The study of the making of corn (Zea mays Indurata) extract yoghurt by adding 2%, 4%, 6% 8% and 10% honey concentration had been done. The purpose of this study is to find the precise honey concentration to produce corn yoghurt with good quality according to SNI 2981:2009. This study consist of 5 treatments and 3 replications, and was designed by factorial complete random design. The data was analysed with varian analysis with F test and DNMRT test with significancy level of 5%. Measurement included corn extract, starter and corn yoghurt. The result of the study showed that the nutrients content of corn yoghurt with 2%-10% honey concentration has meet SNI 2981:2009 standart. The highest nutrient content was corn yoghurt with 10% honey concentration, with content analysis result : protein 3,15%, fat 2,73%, total solid 20,54%, pH 3,8, total lactic acid 0,85%, ash 0,32%, rough fiber 4,49%, vicosity 4,66 dPa.s, total lactid acid bacterias 5,3x108 CFU/ml and total plate 6,6 x 108 (CFU/ml). The organoleptic test shown that the most preferable is corn yoghurt with 8 % honey concentration with the score of appearance 3,7, taste 3,6, consistensy 3,9, colour 3,7 and flavour 3,6.